WIDOWHOOD IN MANCHEGA RURAL SOCIETY. MARRIAGE AND SOCIAL REPRODUCTION STRATEGIES AT THE END OF THE ANCIENT REGIME - Simón García, Maria (Revista de Historia Social y de las Mentalidades, 2025)
This article tries to enter itself in the social fr amework of the population through the  widowhood, not only like a demographic accident, bu t like a life form, an identity, a social  construction. For the social study of the widowhood the crossing of diverse types of  documentary sources will be necessary. In this meth odology the parochial, notarial and cadastral  registries acquire a transcendental importance in t he analysis of the vital cycle of the widowers  and widows. Age, gender, descendants or patrimony w ill be the pillars around which it turns this  proposal of study. One is to catch behaviors and so cial processes of mobility and social  reproduction. Moveove we will try to explain not on ly relationships concerning family, kinship  and dependency, but also solidarity and reciprocity . The married alliance becomes the best  channel of patrimony in which kinship, consanguinit y and affinity are tools of analysis of the  remarriage. For social groups the marriage was a si gnal agent of the property, where patrimony,  marriage and inheritance acted like mechanisms of s ocial mobility and reproduction of the  system constituted in the hierarchial structuring a nd the inequality. Nevertheless other more  underprivileged groups considered the alliance marr ied as a vital strategy of survival.
Keywords: Widowhood; marriage; family; vital traje ctories; social strategies